Kedudukan Aset Kripto sebagai Sarana Penyembunyian Hasil Tindak Pidana Pencucian Uang ( Studi Kasus Putusan Nomor 111/Pid.B/2022/PN Kbm jo. Putusan Nomor 97/Pid/2023/PT SMG) - Ananda Putri; Bintang Wicaksono Ajie (PT Elaborium Elevasi Indonesia, 2026)
This research aims to analyze the legal position of cryptocurrency assets and their use as a means of concealing proceeds from money laundering offenses, using the Kebumen District Court Decision No. 111/Pid.B/2022/PN Kbm in conjunction with the Semarang High Court Decision No. 97/PID/2023/PT SMG as a case study. The research uses a normative juridical method, examining positive legal norms through library research, focusing on Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering, as well as regulations from Bappebti (and later OJK) regarding cryptocurrency assets. The research findings indicate that the court classified cryptocurrency assets as